How positive is their future? Assessing the role of social support and optimism in patients with cardiovascular disease - Putra, Rahman Pranovri; Sudirman, Subhan Ajrin; Fadhilah, Fadhilah (Faculty of Psychology, Universitas Negeri Yogyakarta, 2023)
Someone with coronary heart disease is someone who has a heart defect that makes the heart experience narrowing or inhibition of arteries that drain blood to the heart muscle. This situation may affect the optimism of life that exists in coronary heart patients. However, if coronary heart patients get social support from their partners, it can have a good impact on the level of life optimism. This study aims to determine whether there is a relationship between spousal social support and life optimism in coronary heart disease patients in Pekanbaru City, Riau. This study uses correlational quantitative research methods. The population in this study amounted to 213 people and the sample amounted to 139 people. The sample was determined using non-probability sampling technique. Then, the data were analyzed using Pearson Product Moment correlation analysis. The results of this study indicate that the level of Partner social support is in the high category and life optimism is in the moderate category. Then, the results of the correlation test between partner social support and life optimism obtained a p value = 0.044 and a correlation coefficient value of 0.141. This shows that the proposed research hypothesis is accepted, namely that there is a positive relationship between partner social support and life optimism in patients with cardiovascular disease.